PENGARUH KECAKAPAN LITERASI MEDIA GURU TERHADAP PENGUATAN PENDIDIKAN KARAKTER ANAK PADA TK AISYIYAH KOTA MAKASSAR - Sri Sufliati Romba; Nurul Inayah Aniskamah; Surya Dharma (Universitas Indraprasta PGRI, 2022)
This study was conducted with the aim of knowing the effect of teacher media literacy skills on strengthening character education in Aisyiyah Kindergarten in Makassar City. The population in this study were teachers of Aisyiyah Kindergarten in Makassar, amounting to 135 teachers spread from 47 Aisyiyah Kindergarten and in obtaining research samples using purposive random sampling technique which previously obtained a number of samples using the Slovin formula as many as 57 teachers. The data collection technique was obtained by using a like-art scale questionnaire whose instrument development procedures included validity testing using a gregory testing model and construct validity using Confirmatory Factor Analysis (CFA) and reliability testing using the Alpha Cronbach formula which resulted in a reliability coefficient value of 0.98 for the teacher's digital literacy skill instrument and a reinforcement value of 0.97 for the instrument's instrument character. The data collected were analyzed using inferential statistics, namely simple regression analysis. The results of the study revealed that water had a positive and significant effect on teacher media literacy skills on strengthening character education in Aisyiyah Kindergarten in Makassar City